COMPARISON BETWEEN ROBOTIC ASSISTED LAPAROSCOPIC PYELOPLASTY AND LAPAROSCOPIC PYELOPLASTY AS STANDARD OF CARE FOR PELVI-URETERIC JUNCTION OBSTRUCTION: HOSPITAL-BASED COHORT STUDY. - Pankaj, Kumar; Verma, Neha; Manjunath K; Jumde, Suvit Suresh; Dutta, Rishin; Kulkarni, Prashanth M. (Student's Journal of Health Research Africa, 2024)
Introduction Pelvi-Ureteric Junction Obstruction (PUJO) is a significant clinical difficulty that frequently necessitates surgical treatment. This study examines and contrasts the efficacy of Robotic-Assisted Laparoscopic Pyeloplasty (RALP) and Laparoscopic Pyeloplasty (LP) in treating this problem. The objective is to assess perioperative parameters and patient outcomes to identify the most effective technique for controlling PUJO. Methods The study comprised individuals diagnosed with PUJO who were scheduled to undergo surgical intervention. The study included a total of 48 patients, with 32 of them undergoing LP and the remaining 16 getting RALP. Results 48 patients (32 LP, 16 RALP) aged 10-70 years were studied, with mean ages of 34.28 (LP) and 39.38 (RALP), a male-to-female ratio of 2.2:1, and success rates of 90.63% (LP) and 93.75% (RALP) in transitioning from an obstructed (TYPE 2) to a normal (TYPE 1) O' The RALP group had a longer mean operative time (226.87 ± 32.39 minutes) than the LP group (186.53 ± 33.58 minutes). The RALP group had better patient outcomes, including faster drain removal time (1.69 ± 1.40 days vs. 3.75 ± 1.50 days), shorter hospital stay (2.88 ± 0.88 days vs. 4.06 ± 1.39 days), and somewhat higher success rate (93.75% vs. 90.63%). The success criteria were an obstructed (TYPE 2) to normal (TYPE 1) O'Reilly Curve within 3 months of surgery. Conclusion Although RALP has a longer operational time, it has been shown to achieve better results than LP in terms of success rate, duration of drain usage, and total length of hospital stay. Recommendations It is recommended that future studies include larger sample sizes and longer follow-up periods to further evaluate the long-term effectiveness of RALP and LP in the management of PUJO.